Pengaruh Celebrity Endorser Dan Iklan Instagram Terhadap Keputusan Pembelian (Studi Kasus Pada Online Shop Championsteall.Id) - Erik Wikatanazal; Pardiman Pardiman; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of Celebrity Endorser and Instagram Ads on Purchasing Decisions on online shop championsteall.id. By carrying out appropriate marketing activities on Instagram can be useful for making purchase decisions so that it will increase online shop sales. This research was conducted in Malang City using a questionnaire as a research instrument to obtain data from consumers. In this study, the criteria for respondents were that respondents had to become followers, and had visited the online shop championsteall.id with a planned sample size of 85 people. Data analysis techniques with the help of SPSS 26 For Windows using Multiple Linear Regression Analysis, Simultaneous Test, Partial Test and Test of the Coefficient of Determination to test the effect of independent and dependent variables. The results showed that the variables Celebrity Endorser and Instagram Ads had a simultaneous effect on purchasing decisions. The results of this study also indicate that there is a partial influence between the Celebrity Endorser and Instagram Ads on purchasing decisions.Keywords: Celebrity Endorser, Instagram Ads, Purchase Decisions